Effect of Temperature and Sonication on The Extraction of Gallic Acid from Labisia Pumila (Kacip Fatimah) - Noor Adilah, Md Salehan; Ahmad Ziad, Sulaiman; Azilah, Ajit (Asian Research Publishing Network (ARPN), 2016)
The increasing demand of herbal based product has created great opportunities for global marketing. Labisia pumila contains a phenolic compounds and it has been proven to have multiple biological effects, such as high antioxidant properties and anti inflammatory activity. The Gallic acid(3,4,5-Trihydroxybenzoic acid) is phenolic compounds that exist in Labisia Pumila. Therefore, it is vital to identify a best extraction technique to maximize the performance of the process. Recently, ultrasound-assisted extraction (UAE) widely reported for the extraction of medicinal plants and herbs due to its economic and green technology. This study was carried out to determine the effect of temperature and duty cycle on the performance of UAE in the extraction of gallic acid from Labisia Pumila (Kacip Fatimah).The sonication regiments ( power intensity and duty cycle) were varied to find maximum gallic acid concentration. The low power intensity at 8.66 W/cm2 was used and several duty cycle (10 to 40%) using ultrasonic processor Q700 (700 watts, 20kHz) provided by QSonica, Newtown, U.S.A with a replaceable flat tip ultrasonic probe (sonotrode) made of titanium alloy that had a tip diameter of 12.7 mm and 127 mm length. As the result, the best condition that has been determined for maximum gallic acid extraction was 100 0C with sonication with (0.26±0.02)% w/w or 2630.18 mg/kg . Besides that, the sonication was improved the gallic acid extraction for both 80 0C and 100 0C by 1.4 and 1.5 fold increament respectively .By comparing the effect of temperature, the higher tempperature give the better extraction yield for both with and without sonication. Based on the result can be concluded that, sonication was improved the extraction yield without any chemical aid.